2021
DOI: 10.18549/pharmpract.2021.1.2170
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing errors in Lebanese community pharmacies: incidence, types, underlying causes, and associated factors

Abstract: Objectives: To assess the incidence, types, the causes of as well as the factors associated with dispensing errors in community pharmacies in Lebanon. Methods: An observational cross-sectional study was conducted in 286 pharmacies located all over Lebanon. Data were collected by senior pharmacy students during their experiential learning placement. Collected data included information on the types of dispensing errors, the underlying causes of errors, handling approaches, and used strategies for dispensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Using the generic name in prescribing is an indicator of rational prescribing. It promotes access and affordability of drugs, thereby encouraging treatment adherence 37 38. In a study conducted by Nwolisa et al in Nigeria, they reported that the difference in the cost between the same drugs prescribed in generic names against brand names was between 60% and 41.7%, respectively 30.…”
Section: Discussionmentioning
confidence: 99%
“…Using the generic name in prescribing is an indicator of rational prescribing. It promotes access and affordability of drugs, thereby encouraging treatment adherence 37 38. In a study conducted by Nwolisa et al in Nigeria, they reported that the difference in the cost between the same drugs prescribed in generic names against brand names was between 60% and 41.7%, respectively 30.…”
Section: Discussionmentioning
confidence: 99%
“…There are 37 articles that discuss the incidence of MEs and their factors in Asia, where the articles consist of 9 articles from Southeast Asia [10][11][12][13][14][15][16][17][18] ; 3 articles from East Asia [19][20][21] ; 7 articles from South Asia [22][23][24][25][26][27][28] and 18 articles from West Asia [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] . A total of 2 articles discuss the incidence of MEs and their factors in Australia [47][48] .…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Time pressures and workloads were previously reported to affect the quality of interventions/services provided by the pharmacist. 65 , 66 The perception of “lack of time”, reported as a barrier for service provision, must be taken into consideration through both better management and task redistribution for providing additional contemporary professional services. 65 , 67 …”
Section: Discussionmentioning
confidence: 99%
“… 65 , 66 The perception of “lack of time”, reported as a barrier for service provision, must be taken into consideration through both better management and task redistribution for providing additional contemporary professional services. 65 , 67 …”
Section: Discussionmentioning
confidence: 99%